Institute of Mathematical Statistics Collections 2008
DOI: 10.1214/193940307000000383
|View full text |Cite
|
Sign up to set email alerts
|

Brownian motion on disconnected sets, basic hypergeometric functions, and some continued fractions of Ramanujan

Abstract: Motivated by Lévy's characterization of Brownian motion on the line, we propose an analogue of Brownian motion that has as its state space an arbitrary closed subset of the line that is unbounded above and below: such a process will be a martingale, will have the identity function as its quadratic variation process, and will be "continuous" in the sense that its sample paths don't skip over points. We show that there is a unique such process, which turns out to be automatically a reversible Feller-Dynkin Marko… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…Note that the way (8) in which we define the extension guarantees that the functioñ( , ) is progressively measurable. In [2] the authors then defined the solution of the Δ-stochastic differential equation indicated by the notation…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the way (8) in which we define the extension guarantees that the functioñ( , ) is progressively measurable. In [2] the authors then defined the solution of the Δ-stochastic differential equation indicated by the notation…”
Section: Definitionmentioning
confidence: 99%
“…on the time scale ∈ T. Let us consider an extension of the (probably random) function ( ) as in (8). Let us define the so obtained extension function to bẽ( ).…”
Section: Change Of Measure and Girsanov's Theorem On Time Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…While these are valuable tools, there is an increasing interest in non-uniform time domainsdomains which contain non-uniformly spaced discrete points or a mixture of discrete and continuous parts [4]. Applications include adaptive control [5], real-time communications networks [6], [7], dynamic programming [8], switched systems [9], control theory [10], [11], [12], [13], [14], [15], signal analysis [16], [17], stochastic models [18], population models [19], and economics [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…The goal is not to simply reprove existing, well-known theories, but rather to view R and Z as special cases of a single, overarching theory and to extend the theory to dynamical and control systems on these more general domains. Doing so reveals a rich mathematical structure which has great potential for new applications in diverse areas such as adaptive control [20], real-time communications networks [21], [22], dynamic programming [34], switched systems [30], stochastic models [5], population models [37], and economics [3], [4]. The focus of this paper is the study of linear state feedback controllers [28], [35] in this generalized setting and to compare and contrast these results with the standard continuous and uniform discrete scenarios.…”
Section: Introductionmentioning
confidence: 99%